Risk Analysis of Topo Local Onion Farming in Topo Village, Tidore District, Tidore Islands City - Muhammad, Munawir; Ekaria, Ekaria; Thaib, Nurul Febriani (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Seing the local potential that is owned by people of Topo Village, Tidore Island City, it is necessary to carry out special research related to the Risk Analysis of Topo local shallot farming. This risk analysis research is very important considering of many factors that causes the failure of local topo shallot farming. The research purposes is to determine the farming and to analyze the production risks, cost and income of topo local shallot farming in Topo Village, Tidore Islands City. The methods used in this research are farm analysis and risk analysis. The results of this research are the average of production cost in five times productions process used in the topo local shallot farming in Topo Village is Rp. 184,475,500, with a total production of 10,265 kg so the income obtained by farmers is Rp. 331,532,500/growing season. For the risk analysis, the highest risk is the cost risk with a coefficient of variation by 8.6, this is due to the high cost of production. Meanwhile, the smallest level of risk is in the risk of production, the causes is topo local shallot production which tends to be stable with a coefficient variation of 0.71. In addition, income risk has a lower coefficient of variation of 3.6 than cost risk.